2014
DOI: 10.1002/maco.201407627
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of mild steel by methyl violet and bromide ion in sulfuric acid solution

Abstract: The corrosion inhibition behavior of methyl violet in the absence and presence of bromide ion on mild steel in sulfuric acid solution has been studied by weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy. The results indicate that the corrosion of mild steel is obviously reduced by methyl violet in combination with bromide ion. Electrochemical studies show that methyl violet and bromide ion act as mixed type inhibitors retarding the cathodic and anodic corrosion reactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…This remarkable improvement could be due to the synergistic adsorption of FYPA and iodine ions. As expected, the C dl value tended to decrease in the presence of FYPA and combination with KI, resulting from a decrease of the local dielectric constant or the increase of the thickness of the electrical double‐layer capacitor . The results revealed that the inhibitor molecules were adsorbed on the steel surface acting at the interface electrode and solution.…”
Section: Resultssupporting
confidence: 61%
“…This remarkable improvement could be due to the synergistic adsorption of FYPA and iodine ions. As expected, the C dl value tended to decrease in the presence of FYPA and combination with KI, resulting from a decrease of the local dielectric constant or the increase of the thickness of the electrical double‐layer capacitor . The results revealed that the inhibitor molecules were adsorbed on the steel surface acting at the interface electrode and solution.…”
Section: Resultssupporting
confidence: 61%
“…As shown in Table , the values of R ct and η z increased significantly with increasing the concentration of inhibitor, and the maximum η z was as high as 95.93% when the concentration of PAQ reaches up to 3.24 mM, which shows that the inhibitor molecules can effectively inhibit the corrosion of Q235 steel in hydrochloric acid solution. Comparatively, the C dl value trends to decrease as expected with the increase of inhibitor concentration, which results from the decrease in local dielectric constant or an increase in the thickness of electrical double layer capacitor . It is revealed that the inhibitor molecules instead of water molecules on the steel surface and take effect by adsorption at the electrode/solution interface.…”
Section: Resultsmentioning
confidence: 64%